TFTIA Work Plan - TFTIA Co-Chairs (Arctic Council Secretariat, 2016)
Work plan for the year 2015-2017, submitted by the Arctic Council Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) to the Senior Arctic Officials meeting in Fairbanks, Alaska, 16-17 March, 2015.